Employees' satisfaction as influenced by acoustic and visual privacy in the open office environment - Soules, Maureen Jeanette (My University, 2014)
The purpose of this study was to examine the relationship between employees' acoustic and visual privacy issues and their perceived satisfaction in their open office work environments while in focus work mode. The study examined the Science Teaching Student Services Building at the University of Minnesota Minneapolis. The building houses instructional classrooms and administrative offices that service UMN students. The Sustainable Post-Occupancy Evaluation Survey was used to collect data on overall privacy conditions, acoustic and visual privacy conditions, and employees' perceived privacy conditions while in their primary workplace. Paired T-tests were used to analyze the relationships between privacy conditions and employees' perceptions of privacy. All hypotheses are supported indicating that the privacy variables are correlated to the employees' perception of satisfaction within the primary workplace.The findings are important because they can be used to inform business leaders, designers, educators and future research in the field of office design.
University of Minnesota M.S. thesis. August 2014. Major: Design, Housing and Apparel. Advisor: Denise A. Guerin, PhD. 1 computer file (PDF); viii, 103 pages, appendices A-B.
Keywords: Acoustic; Office; Privacy; Satisfaction; Visual; Design, housing and apparel; Interior Design